ASPECTE FORMATIVE ALE EXCURSIILOR ÎN ÎNVĂŢĂMÂNTUL PRIMAR - USM ADMIN (Studia Universitatis Moldaviae: Stiinte ale Educatiei, 2008)
The integration of lessons-excursions in projection of didactic activities for teachers of primary classes encourages formation of different abilities of primary pupil: development of curiosity and creativity, formation of practical skills to effect observation, to compare objects, capitalization of experience of knowledge, accumulation of new knowledge, skills, abilities, attitudes, and investigational behaviors’ (scientific work). The proposal of one plan far -reaching (yearly) alternative shows real possibilities of realization curriculum contents at fundamental disciplines with accent on organi- zation forms of type lesson -excursions.